Predicting Impulsive Buying in Tokopedia Flash Sales: A UTAUT2 Approach - M. Bintang Naufal Riansyah; Mira Afrina; Ken Ditha Tania; Rizka Dhini Kurnia (Universitas Islam Indragiri, 2026)
Flash sale events have become a dominant marketing strategy to trigger rapid purchasing decisions. However, despite the massive growth of e-commerce in Indonesia, it remains unclear whether consumer participation in these events is primarily driven by the thrill of the